Measurement of the ZZ production cross section in proton-proton collisions at s√= 8 TeV using the ZZ→ℓ−ℓ+ℓ′−ℓ′+ and ZZ→ℓ−ℓ+νν¯ channels with the ATLAS detector - Aaboud, M. (2017)
A measurement of the ZZ production cross section in the ` − ` + ` 0 − ` 0 + and ` − ` + νν̄ channels (` = e, μ) in proton?proton collisions at s = 8 TeV at the Large Hadron Collider at CERN, using data corresponding to an integrated luminosity of 20.3 fb −1 collected by the ATLAS experiment in 2012 is presented. The fiducial cross sections for ZZ → ` − ` + ` 0 − ` 0 + and ZZ → ` − ` + νν̄ are measured in selected phase-space regions. The total cross section for ZZ events produced with both Z bosons in the mass range 66 to 116 GeV is measured from the combination of the two channels to be 7.3 ± 0.4 (stat) ± 0.3 (syst) +0.2 −0.1 (lumi) pb, which is consistent with the Standard Model prediction of 6.6 +0.7 pb. The differential cross sections in bins of various kinematic variables are presented. The differential event yield as a function of the transverse momentum of the leading Z boson is used to set limits on anomalous neutral triple gauge boson couplings in ZZ production.